The Role of Pre-Marital Guidance in Shaping a Sakinah Family - Ummah, Evi Mi'rojatul (At-Taujih: Jurnal Bimbingan dan Konseling Islam, 2025)
This research aims to examine the role of pre-marital counseling in forming a sakinah family at the Office of Religious Affairs (KUA) Selong, East Lombok. A sakinah family is the goal of marriage in Islamic teachings, characterized by tranquility, peace, and lasting happiness. Pre-marital counseling is considered one of the strategic efforts to realize a sakinah family by providing knowledge, skills, and understanding to prospective couples about a harmonious household life in accordance with religious values. The research method used is qualitative, a case study type of research with data collection techniques through in-depth interviews, observation, and documentation. The subjects of the research consisted of engaged couples participating in pre-marital counseling, religious counselors, and KUA Selong officers. The research results indicate that the pre-marital counseling organized by KUA Selong plays a significant role in forming a sakinah family. Through this guidance, prospective couples gain a better understanding of the concept of a sakinah family, the responsibilities of husband and wife, effective communication, conflict management, and the importance of maintaining a balance between spiritual and material needs. In addition, premarital counseling also provides insights into the importance of the roles and functions of the family in building a harmonious and civilized society. Keywords: Pre-marital counseling, Sakinah family